Estimation of hazardous concentration of toluene in the terrestrial ecosystem through the species sensitivity distribution approach. (15th November 2021) - Chae, Yooeun; Kim, Lia; Lee, Jieun; Kim, Dokyung; Cui, Rongxue; An, Youn-Joo
Abstract: Toluene is a highly flammable and commonly used industrial chemical with severe health consequences on humans upon exposure and ingestion. In this study, multispecies bioassays were conducted using a species sensitivity distribution approach to determine acute and chronic hazardous concentrations of toluene in soil. Acute and chronic toluene toxicity tests were conducted with seven soil species from four taxonomic groups. The results from the toxicity tests were used to estimate the acute and chronic HC5 (hazardous concentration for 5 % of species) of toluene in the terrestrial environment at 58.9 (5.4–639.6) mg kg −1 and 2.2 (0.2–19.8) mg kg −1, respectively. To the best of our knowledge, this is the first study to estimate the hazardous concentration of toluene in soil by conducting a battery of bioassays. These values can be used as references for the environmental risk assessment of chemical accidents involving toluene and estimating its impact on soil to protect the terrestrial environment. Graphical abstract: Image 1 Highlights: Bioassays with multiple test species were conducted to estimate toluene toxicity. Toluene soil hazard concentrations were found by species sensitivity distribution. Acute and chronic HC5 of toluene were calculated as 58.9 and 2.2 mg kg −1 Hazardous chemical management is necessary for protection from chemical accidents. Toluene HC5 values can be used as reference values for risk and impact assessment. Abstract : In this study, acute and chronic hazardous concentrations of toluene were estimated to protect soil ecosystems based on species sensitivity methods.